Structure elucidation of the syringafactin lipopeptides provides insight in the evolution of nonribosomal peptide synthetases. Issue 48 (4th December 2019) - Götze, Sebastian; Arp, Johannes; Lackner, Gerald; Zhang, Shuaibing; Kries, Hajo; Klapper, Martin; García-Altares, María; Willing, Karsten; Günther, Markus; Stallforth, Pierre
Abstract : A snapshot of evolution in flagrante shows that recombination within and between biosynthetic genes leads to diversification of nonribosomal peptides. Abstract : Modular biosynthetic machineries such as polyketide synthases (PKSs) or nonribosomal peptide synthetases (NRPSs) give rise to a vast structural diversity of bioactive metabolites indispensable in the treatment of cancer or infectious diseases. Here, we provide evidence for different evolutionary processes leading to the diversification of modular NRPSs and thus, their respective products. Discovery of a novel lipo-octapeptide family from Pseudomonas, the virginiafactins, and detailed structure elucidation of closely related peptides, the cichofactins and syringafactins, allowed retracing recombinational diversification of the respective NRPS genes. Bioinformatics analyses allowed us to spot an evolutionary snapshot of these processes, where recombination occurred both within the same and between different biosynthetic gene clusters. Our systems feature a recent diversification process, which may represent a typical paradigm to variations in modular biosynthetic machineries.